2005
DOI: 10.1110/ps.04990205
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen exchange and ligand binding: Ligand‐dependent and ligand‐independent protection in the Src SH3 domain

Abstract: Amide hydrogen-deuterium exchange has proven to be a powerful tool for detecting and characterizing high-energy conformations in protein ensembles. Since interactions with ligands can modulate these highenergy conformations, hydrogen exchange appears to be an ideal experimental probe of the physical mechanisms underlying processes like allosteric regulation. The chemical mechanism of hydrogen exchange, however, can complicate such studies. Here, we examine hydrogen exchange rates in a simple model system, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…15,16,[57][58][59] Long-range propagation of conformational tightening would therefore produce an amplification of the local energy changes of single-point mutations. Unfortunately, however, the comparative NMR relaxation study shown here for the SPCp41 chimera and the P7A mutant does not provide us with information about long-range effects in the SH3 domain brought about by the slow aggregation of the mutant chimera, which hindered a more thorough analysis of the data.…”
Section: The Thermodynamic Impact Of Pro-ala Substitutions Upon the Smentioning
confidence: 99%
“…15,16,[57][58][59] Long-range propagation of conformational tightening would therefore produce an amplification of the local energy changes of single-point mutations. Unfortunately, however, the comparative NMR relaxation study shown here for the SPCp41 chimera and the P7A mutant does not provide us with information about long-range effects in the SH3 domain brought about by the slow aggregation of the mutant chimera, which hindered a more thorough analysis of the data.…”
Section: The Thermodynamic Impact Of Pro-ala Substitutions Upon the Smentioning
confidence: 99%
“…However, in the presence of HA 8 , the ligand can stabilize the folded (closed) form of the protein, thereby preventing additional deuterium uptake in the complex relative to the free protein. 46 It is also this phenomenon which allows binding affinities to be determined by PLIMSTEX studies. 47 Previous work has identified five critical amino acids necessary for Link_TSG6 HA-binding by site-directed mutagenesis (Lys11, Tyr12, Tyr59, Phe70 and Tyr78), and confirmed with NMR studies wherein eleven amino acids (Lys11, Tyr12, Val57, Tyr59, Pro60, Ile61, Phe70, Ill76, Tyr78, Arg81 and Trp88) were found to interact with the ligand.…”
mentioning
confidence: 99%
“…These data suggest that changes in the structure or dynamics of the N-terminal region Interestingly, no such ligand-induced structural changes are evident from X-ray crystallography data [38]. It is also possible that ligand binding leads to a depopulation of some of the conformers, as this also can influence HDX rates [14].…”
Section: Tcda-a2 and Its Interaction With Cd-greasementioning
confidence: 92%
“…When a ligand binds to a protein, some of the amide H's may become (more) protected against exchange (due to the formation of new or stronger inter-or intramolecular H-bonds or a reduction in solvent accessibility), resulting in decreased rates of exchange for the peptides containing these groups [10,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation